PENUMBUHAN KARAKTER CINTA ALAM DALAM KEGIATAN EKSTRAKURIKULER IKATAN PELAJAR PECINTA ALAM (IPPA) DI MAN 1 BANJARNEGARA (Civic Education Program, Universitas Negeri Semarang, 2022)
Character is a trait possessed by a person as a characteristic that describes a person in behaving and acting in his environment. The character of love nature is an attitude and behavior that maintains and preserves the surrounding nature. The indicator of love nature is by carryying out adventure activities and challenges that are directed at efforts to protect and preserve nature. The purpose of thiis research is to describe the growth of love nature character in extracurricular activities of Student Bond of Nature Lover (IPPA) in Islamic Senior High School 1 Banjarnegara. This research used qualitative method. Data collecting by observation, interviews, and documentation. Data analysis techniques with data collection, data reduction, data presentation, and conclusions. The research results showed that the growth of the love nature character in extracurricular activities of Student Bond of Nature Lover (IPPA) in Islamic Senior High School 1 Banjarnegara through work program under the responsibility of growing the character of the daily management, growing the character of the skill development division, growing character of the environment forests and mountains division, growing character of the equipment division, growing character of the enterpreneurship division, growing character of the public relations and documentation division, by teaching, exemplary and habituation to members and character values in every activity of Student Bond of Nature Lover (IPPA) in Islamic Senior High School 1 Banjarnegara.